Phase centre variation of the GNSS antenna onboard the CubeSats and its impact on precise orbit determination - Allahvirdizadeh, Amir (2021)
CubeSats as small Low Earth Orbiting (LEO) satellites are equipped with space-based receiver and antenna capable of tracking Global Navigation Satellite Systems (GNSS). These GNSS signals provide the possibility of precise orbit determinations (POD) of the CubeSats which is essential for different earth and space science applications. Examples of these applications are monitoring the movement of the Earth’s surface and oceans using Interferometric Synthetic Aperture Radar (InSAR) and GNSS reflectometry, weather forecasting using GNSS Radio Occultation, satellites rendezvous and docking in orbits, and attitude and relative motion control of the CubeSats in a formation flying. The nominal antenna phase centre variations (PCV) as direction-dependent delays in the GNSS observations are generally determined using ground calibration methods such as the anechoic chamber and robotic tests. However, these methods do not consider the actual space environment and multipath effects due to the CubeSat structure, and neighboring space vehicles in orbit. In this contribution, the empirical PCV pattern for the GNSS antenna onboard a set of CubeSats that are flying in a mega-constellation are determined using the residual approach and compared with the nominal values derived from ground calibrations. The estimated PCV values based on in-flight GNSS observations more realistically represent the near-field effects than the ground calibrated values. The new bin-wise PCV pattern is used in an iteratively POD procedure to determine the precise orbits of the CubeSats. Internal validation methods such as those analyse the overlapping orbits, the posterior variance factors, and the observation residuals confirm the benefits of the proposed PCV patterns. The estimated orbits using these patterns have shown higher accuracies compared with the derived orbits using the nominal PCV values.